The Effectiveness of Restorative Justice Mediation as a Resolution Effort for General Criminal Cases by Polres Satreskrim Investigators Jombang - Santoso, Alvian Hidayat (Police Studies Review, 2024)
General criminal cases that occur in the jurisdiction of the Jombang Police are still classified high which causes the number of arrears of cases to increase every year. Study This aims to describe the application of the principles of restorative justice, identifying factors that influence the effectiveness of restorative justice mediation, and obstacles or obstacles to implementation of restorative justice mediation as an effort to resolve general criminal acts by investigators Jombang Police Criminal Investigation Unit. This type of research is qualitative descriptive with a juridical approach normative. The research results show active community involvement through internal mediation resolution of general criminal acts in order to seek mutual agreement through deliberation and consensus through the implementation of restorative justice by the Jombang Police Criminal Investigation Unit. During the implementation of mediation restorative justice at the Jombang Police is still not effective because there are several factors influencing it, including legal factors, law enforcement, legal facilities, society, and culture. The restorative justice reform system is also not running completely smoothly because there are obstacles or obstacles that are vulnerable to being used as openings for corruption.